Fostering Community Inclusion through Parental Engagement: A Case Study from Klaten, Indonesia - Abdul Malik, Hatta; Riyadi, Agus; Karim, Abdul (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study sets out to evaluate the impact of parental participation on the welfare of children with disabilities in community-based rehabilitation programs. The research seeks to answer the following questions: First, how does parental involvement facilitate the rehabilitation process at the Karanganom District Inclusion Centre (ICKK), Klaten Regency, and second, how does such participation contribute to fulfilling the rights of children with disabilities? The study adopts a qualitative descriptive method with a case study approach. A comprehensive data collection approach was employed, encompassing in-depth interviews with 15 parents actively involved in the rehabilitation program, participatory observations of rehabilitation activities, and a thorough analysis of policy documents and program reports. The research findings underscore the multifaceted nature of parental involvement, highlighting its role in providing direct assistance in therapy sessions, facilitating life skills training for children, and fostering participation in parent support groups. Concretely, this involvement has been found to enhance children's communication, motor, and independence skills in daily activities.Furthermore, parents advocate for children's access to inclusive education and health services. However, limited access to resources and the capacity of parents to support rehabilitation remain significant challenges. This study acknowledges the potential for bias in data interpretation, given parents' dual role as participants and evaluators. Consequently, further research involving the perspective of rehabilitation professionals is necessary to provide a more objective picture. The findings of this research underscore the necessity for more comprehensive policies to enhance the capacity of parents as strategic partners in the rehabilitation of children with disabilities.